Evaluasi Hasil Belajar Menggunakan Tes dan Non Tes Perspektif Pendidikan Islam - Moh. Iqbal Maulidy; Dini Permana Sari (Mimbar Kampus: Jurnal Pendidikan dan Agama Islam, 2024)
There are two techniques for evaluating student learning outcomes: evaluation with test and non-test techniques. The objectives of the writing include understanding the characteristics of learning outcome evaluation, knowing the cognitive, affective, and psychomotor domains as the object of learning evaluation, knowing the main steps in learning outcome evaluation, and understanding the application of learning outcome evaluation, both test, and non-test. This paper is useful for students, namely it can add insight for students about test and non-test techniques as a tool for evaluating learning outcomes. The method used in this study is library research. Research is carried out by collecting information and data from various sources such as reference books, similar previous research results, articles, notes, and numbers related to the problem to be solved. The evaluation of learning in modern times in Islamic education shows an effort to adapt to the times, making education more relevant and responsive to the needs of society. Evaluation not only serves to provide value but also to provide constructive feedback. This helps students understand their strengths and weaknesses and how to improve them. Keywords: Evaluation; Islam; learning; non test; teacher; test